Metamorphosis - Kafka, Franz, 1883-1924.; Project Gutenberg (Salt Lake City : Project Gutenberg Literary Archive Foundation, 2008)
Gregor Samsa wakes up one morning to find he has been transformed into a gigantic insect. This tale of imagination was written against the backdrop of increasing turmoil in central Europe and remains not just an affecting tale but a disturbing allegory.
Human-read audiobook.
Mode of access: World Wide Web.
Keywords: Metamorphosis -- Fiction; Alienation (Social psychology) -- Fiction; Self-sacrifice -- Fiction; Audiobooks